2015
DOI: 10.1016/j.plabm.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter comparison of automated procalcitonin immunoassays

Abstract: ObjectivesA multicenter study to compare results of BRAHMS Kryptor PCT with those obtained using four BRAHMS-partnered procalcitonin (PCT) automated immunoassays (DiaSorin Liaison, BioMérieux Vidas, Roche Cobas E601 and Siemens Advia Centaur) and the Diazyme immunotubidimetric assay implemented on four clinical chemistry platforms (Abbott Architect c16000, Siemens Advia 2400, Roche Cobas C501 and Beckman Coulter AU5800).Design and methodsOne hundred serum samples from in-patients with PCT values between 0.10 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 12 publications
2
42
0
Order By: Relevance
“…In our subgroup analysis, we failed to get exact age and sex information from some of the studies, which hindered the analytical process going further [21,26,31,33,36,37,40,41,54]. Our results assessing the performance of different PCT assays were in line with previous studies which demonstrated equivalence among 3 different PCT assays (Kryptor, Vidas, or Elecsys/-Cobas), as the threshold and accuracy were suggested consistent across these three tests in our study [55,56]. A study comparing recent popular PCT assay systems showed the results from these systems correlated well, but their regression lines varied considerably.…”
supporting
confidence: 82%
“…In our subgroup analysis, we failed to get exact age and sex information from some of the studies, which hindered the analytical process going further [21,26,31,33,36,37,40,41,54]. Our results assessing the performance of different PCT assays were in line with previous studies which demonstrated equivalence among 3 different PCT assays (Kryptor, Vidas, or Elecsys/-Cobas), as the threshold and accuracy were suggested consistent across these three tests in our study [55,56]. A study comparing recent popular PCT assay systems showed the results from these systems correlated well, but their regression lines varied considerably.…”
supporting
confidence: 82%
“…Notably, even if differently available PCT immunoassays produce consistent analytical result several studies have been carried out to evaluate the analytical performance and the possible implications on clinical classification of patients using different methods. 36 Overall, the published studies showed a satisfactory analytical alignment between BRAHMS PCT Kryptor and the other methods (r ≥ .9) with good agreements (>80%) in patient classification at the 3 conventional diagnostic thresholds for diagnosis of bacterial infections 0.50, 2.0 and 10 ng/mL, 37 but the unavoidable modest analytical bias between different IMAs suggests the use of the same method for longitudinal patient monitoring. In addition, no data on agreement between different methods are available in patients carrying thyroid nodules and MTC.…”
Section: Discussionmentioning
confidence: 90%
“…The results of the comparison study with BRAHMS PCT-sensitive Kryptor were especially surprising and favorable. Overall, the correlation coefficient was excellent (i.e., r = 0.999; p < 0.001) and the bias extremely limited, lower than 5% (i.e., 3.2%), and thus even better than those frequently observed when comparing other methods using the same BRAHMS anti-PCT monoclonal antibodies [12,13,16,17]. Identical conclusions can be made for diagnostic agreement at the three clinical decision thresholds, whereby global agreement between Access PCT and BRAHMS PCT-sensitive Kryptor was always ≥98%, again, better than comparative methods based on BRAHMS anti-PCT monoclonal antibodies.…”
Section: Discussionmentioning
confidence: 68%
“…The well-established value of PCT measurement in many infectious conditions and across a kaleidoscope of healthcare settings has strongly contributed to development of analytical techniques for its measurement [11]. More specifically, a large number of fully-automated immunoassays have become commercially available during the past decade, employing different assay formats (i.e., enzymatic, luminescent, fluorescent, chemiluminescent and turbidimetric immunoassays) [12][13][14][15][16][17][18][19]. Since the clinical management of patients with severe infections and/or sepsis is always critical and time-dependent, the availability of fully-automated PCT immunoassays is now virtually unavoidable, and these techniques enable an excellent balance between high throughput, short turnaround time, low sample volume (which is always crucial in critical patients needing repeated blood collections) and reasonable costs.…”
Section: Introductionmentioning
confidence: 99%